The Effect of TikTok on English Pronunciation of EFL Secondary School Learners - Sulistiani, Tamara; Syahid, Abdul; Qamariah, Zaitun (Universitas Pahlawan Tuanku Tambusai, 2025)
As technology evolves, its potential to enhance language learning methodologies, particularly in terms of pronunciation, is becoming increasingly apparent. This study investigated whether students taught using TikTok achieved better pronunciation accuracy compared to those taught using YouTube Shorts. A quasi-experimental design with a pretest-posttest approach was employed, involving 46 9th-grade students from a private Islamic high school in Palangka Raya City, Central Kalimantan Province, Indonesia. Students were divided into two groups: one group received a TikTok-based intervention, while the other group used YouTube Shorts as a comparison tool. The results showed that students exposed to TikTok experienced a significant improvement in pronunciation accuracy (p = 0.001, p 0.05) compared to the group using YouTube Shorts. This finding suggests that TikTok, with its interactive and engaging short video format, is more effective in improving pronunciation accuracy and intonation among EFL learners.